Later life learning experiences: listening to the voices of Chinese elders in Hong Kong. Issue 5 (2nd September 2016) - Tam, Maureen
Abstract: Governments' anxieties about ageing populations are mostly concerned with the costs of welfare, care and health provision which all have to be paid for by an ever dwindling working population. However, research in later life learning indicates the significant role that lifelong learning can play in promoting mental well-being and resilience, and in assisting with maintaining personal self-confidence and self-coping strategies that prevent cognitive decline in an ageing population. This paper draws on the research with a group of Chinese elders in Hong Kong, who provide information about their experiences and views on learning in later life, including the meaning of learning, barriers to participation, learning interests, needs, motivations, and instructional preferences. Both quantitative and qualitative findings are reported to shed light on later life learning experiences, which contribute to the global understanding of later life learning and serve to inform the development of policy and practice geared to the planning and provision of opportunities to keep learning at the later stages of life.